2020
DOI: 10.5222/jaren.2020.80764
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Nutrition and Physical Activity Levels and Body Mass Index of Individuals who Prefer Healthy Living Centers in Central Districts of Bursa Province

Abstract: unlu hamur işi tüketimi durumu, beyaz et ağırlıklı beslenmeye dikkat etme ve fastfood besin tüketimi ile BKİ arasında anlamlı ilişki bulunmuştur (p<0,05). Düzenli fiziksel aktivite yapma ile BKİ arasında anlamlı ilişki saptanmamış olmasına rağmen bireylerin yaptığı orta dereceli aktivite ve yürüyüşün dakikasıyla ve bireylerin BKİ değerleri pozitif yönlü korelasyon gösterdiği saptandı (p<0.05). Sonuç: Obezite oranı %61,5 tespit edilmiştir. Geleneksel yeme alışkanlıklarımızın doğru beslenme alışkanlıklarıyla mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The reading food label values of the group with normal BMI values were found to be significantly different. [15], in the thesis study conducted by Er-Döngel with 430 participants, 59.8% of the participants had adequate levels [16], 94.4% of the 195 participants were found to have adequate levels of NL by Ünal [17], in Uzun's thesis study with 967 participants, 73.5% of them were at adequate levels [18], in their study with 320 academic participants, Demir et al found that 50% of them were at an adequate level, 32.8% were at borderline, 17.2% were at inadequate level [19] and Ozdenk reported that 32.1% of the 225 licensed athletes had adequate levels of NL. It was thought that the differences in the results might be due to the differences in the geographical differences where the studies were conducted, the used scales, and the population structure.…”
Section: Resultsmentioning
confidence: 99%
“…The reading food label values of the group with normal BMI values were found to be significantly different. [15], in the thesis study conducted by Er-Döngel with 430 participants, 59.8% of the participants had adequate levels [16], 94.4% of the 195 participants were found to have adequate levels of NL by Ünal [17], in Uzun's thesis study with 967 participants, 73.5% of them were at adequate levels [18], in their study with 320 academic participants, Demir et al found that 50% of them were at an adequate level, 32.8% were at borderline, 17.2% were at inadequate level [19] and Ozdenk reported that 32.1% of the 225 licensed athletes had adequate levels of NL. It was thought that the differences in the results might be due to the differences in the geographical differences where the studies were conducted, the used scales, and the population structure.…”
Section: Resultsmentioning
confidence: 99%